2014
DOI: 10.1097/wnp.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

SIRPIDs

Abstract: This small series suggests that the presence of subclinical status epilepticus and traumatic brain injury correlated with the presence of SIRPIDs signifying that SIRPIDs may be due to a more focal etiology and may represent a more ictal pattern than previously thought. Longer recording times in those patient populations may yield more cases of SIRPIDs in which to base further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In the present study, the rate of SIRPIDs was 14%, which is similar to previous studies after cardiac arrest ( Alvarez et al, 2013 ; Benarous et al, 2019), and in line with the prevalence among critically ill patients ( Alsherbini et al, 2017 , Braksick et al, 2016 , Van Straten et al, 2014 ). SIRPIDs, however, seem to be transient in nature.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the rate of SIRPIDs was 14%, which is similar to previous studies after cardiac arrest ( Alvarez et al, 2013 ; Benarous et al, 2019), and in line with the prevalence among critically ill patients ( Alsherbini et al, 2017 , Braksick et al, 2016 , Van Straten et al, 2014 ). SIRPIDs, however, seem to be transient in nature.…”
Section: Discussionsupporting
confidence: 93%
“…Smaller series have verified the association of stimulusinduced rhythmic, periodic, or ictal discharges and seizures. 13,26 However, a key unanswered question is whether stimulus-induced patterns are more or less associated with seizures than the spontaneous appearance of the periodic or rhythmic pattern. In this study, there was no significant difference in the incidence of seizures when patterns were stimulus-induced compared with spontaneously occurring patterns, but this finding is limited because of the small number of patients with stimulus-induced patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an association between seizures in specific periodic or rhythmic patterns, but these studies are limited in generalizability because of their small sample sizes. [1][2][3][4][5][10][11][12][13][14][15][16] They also do not describe the specific features of these patterns that are associated with risk for seizures. To overcome these limitations, we used a large, multicenter database containing detailed descriptions of cEEG recordings and seizure incidence in critically ill patients.…”
mentioning
confidence: 99%
“…SIRPIDs also stem from many etiologies, the most common being intracerebral hemorrhage, anoxic brain injury, metabolic disturbances, traumatic brain injury, and drug toxicity (Braksick et al, 2016, Hirsch et al, 2004, Van Straten et al, 2014). …”
Section: Stimulus-induced Rhythmic Periodic or Ictal Discharges (Simentioning
confidence: 99%
“…Most studies report a strong association of SIRPIDs with seizures, with 27–51% of patients found to have coexisting spontaneous seizures (Braksick et al, 2016, Hirsch et al, 2004) (and 4/4 patients with SIRPIDs had NCSE in one small study) (Van Straten et al, 2014). However, the largest series of patients on cEEG monitoring found no increased association of seizures in patients with stimulus-induced compared to spontaneous patterns (Rodriguez Ruiz et al, 2016).…”
Section: Stimulus-induced Rhythmic Periodic or Ictal Discharges (Simentioning
confidence: 99%